2005
DOI: 10.1111/j.1399-0039.2005.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α‐, TNF‐β‐, IL‐6‐, and IL‐10‐promoter polymorphisms in patients with chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a major health problem. The disease is driven by abnormal inflammatory reactions in response to inhaled particles and fumes. Therefore, inflammatory mediators are postulated to be of distinct importance. In the present case-control study, we investigated interleukin (IL)-promoter polymorphisms known to correlate with altered transcription levels of their gene products in patients with COPD. We analyzed tumor necrosis factor-alpha (TNF-alpha)-308, TNF-beta-intron1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 41 publications
5
54
1
7
Order By: Relevance
“…Although it has been speculated that there may be a potential glucocorticoid receptor at position Ϫ557 to Ϫ552, the sequence around the Ϫ572 site does not have a strong homology to any known transcriptional factor binding site. Thus, these observations, together with the wealth of IL-6 Ϫ174 genotype-association studies (45)(46)(47)(48)(49)(50), indicate that, in Northern Europeans, the IL-6 Ϫ174 genotype is probably the main promoter polymorphism determining variation in IL-6 induction.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been speculated that there may be a potential glucocorticoid receptor at position Ϫ557 to Ϫ552, the sequence around the Ϫ572 site does not have a strong homology to any known transcriptional factor binding site. Thus, these observations, together with the wealth of IL-6 Ϫ174 genotype-association studies (45)(46)(47)(48)(49)(50), indicate that, in Northern Europeans, the IL-6 Ϫ174 genotype is probably the main promoter polymorphism determining variation in IL-6 induction.…”
Section: Discussionmentioning
confidence: 99%
“…Além da influência do alelo G à função pulmonar, Attaran et al (2010) ressaltam que a IL6 também acelera a libertação de proteínas de fase aguda de resposta inflamatória e piora a condição inflamatória subjacente. Para os sujeitos do grupo CP nossos achados corroboram com os estudos de Seifart et al (2005), o qual também observou maior prevalência do genótipo heterozigoto nos casos em uma população alemã, bem como os resultados apresentados por Colakogullari et al (2008) em um estudo turco. Sabe-se que o polimorfismo estudado no gene que codifica a IL6 está estritamente relacionado com a propensão a doença, além disso, o alelo dito de risco é responsável por aumentar a produção destas citocinas associando-as a processos inflamatórios, um fator na promoção da carcinogênese (ZHOU et al, 2015;JIA et al, 2015).…”
Section: Resultsunclassified
“…Studies in Taiwanese (Huang et al, 1997), Japanese (Sakao et al, 2001), and Caucasian smokers (Gingo et al, 2008) showed similar results to those of the present study in demonstrating that the TNFα-308 polymorphism is a risk factor of COPD. However, studies in Thai (Chierakul et al, 2005), adenovirus C-infected Egyptian (Ezzeldin et al, 2012), Caucasian (Higham et al, 2000;Chappell et al, 2007), German (Seifart et al, 2005), and European-descended American (Tanaka et al, 2007) subjects showed opposite results. Teramoto et al (2008) stated that the TNFα-308 polymorphism was not associated with susceptibility to Asian COPD.…”
Section: Data Are Reported As Number (Percentage) †mentioning
confidence: 94%
“…A common guanine (G) to adenine (A) substitution at position 308 in the TNFα gene promoter (rs1800629) increases gene transcriptional activity (Wilson et al, 1997;Wu and McClain, 1997). This polymorphism has been studied with respect to COPD in several populations, again producing contradictory results (Higham et al, 2000;Sakao et al, 2001;Seifart et al, 2005;Brøgger et al, 2006;Chappell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%